From peer influence to parental roles: factors associated with teenage pregnancy in Dire Dawa city, Eastern Ethiopia - Mawerdi Adem; Saba Hailu; Nega Assefa; Tesfaye Assebe Yadeta (Reproductive Health)
Abstract Background Although teenage pregnancy causes a considerable challenge to young women, studies among sexually active teenagers and the influence of peers on teenage pregnancy are not widely available. This study aims to determine the prevalence of teenage pregnancy and the association between peer pressure and other factors of teenage pregnancy in Dire Dawa secondary school, Eastern Ethiopia. Methods Institutional-based cross-sectional study was conducted among 677 identified sexually active students from selected schools. Census was conducted on 2260 teenagers to identify sexually active teenagers using a stage cluster sampling technique. Sexually active teenagers were recruited using a simple random sampling method. Data was entered into EpiData-version 3.1 and exported to STATA version 16 for analysis. Modified passion regression was done to assess the association between of teenage pregnancy and predictor variables and significantly associated at p-value < 0.05. Result Out of the total sexually active females 135 (19.9%) were pregnant. Teenage pregnancy was higher among teenagers in the 18–19 (APR = 3.21, 95% CI: 2.10–5.18) age group, living with either of their biological parents (APR = 1.9, 95% CI: 1.29–2.69) and neither of the biological parents (APR = 2.7 95% CI: 1.39–3.34), teenagers who had sex due to peer pressure (APR = 2.01, 95% CI: 1.51–2.86) and not knowing the ovation time in the menstrual cycle (APR = 1.6, 95% CI: 1.07–2.28). Teenage pregnancy is lower among teens who have good parent-daughter interaction (APR = 0.6, 95% CI: 0.50–0.91). Conclusion Nearly one-fifth of the students experienced teenage pregnancy. Teenage pregnancy is higher amongst the age group of 18–19, living with either or neither of the parents, having sex due to peer pressure, not knowing the ovulation time, and lower among teens with good parent-daughter interaction. Teenage pregnancy in Dire Dawa is influenced by a combination of individual, peer, and family-related factors. Addressing these through school-based programs, community involvement, and family-centered interventions is crucial to reducing teenage pregnancy rates.